Semi-occlusive dressing for the treatment of fingertip amputations with exposed bone: quantity and quality of soft-tissue regeneration. (June 2014) - Hoigné, D.; Hug, U.; Schürch, M.; Meoli, M.; von Wartburg, U.
Nineteen fingertip amputations with exposed bone were treated with a semi-occlusive dressing. The quantity and quality of the regenerated soft tissue was examined. In all 19 fingers there was sufficient uncomplicated healing such that secondary surgical procedures were not needed. At follow-up 6–18 months after the injury, soft tissue thickness around the bone of the distal phalanx measured 6.0 mm (SD 1.6) on the palmar aspect (opposite side 7.0 mm (SD 0.8)) and 4.2 mm (SD 1.7) distally (opposite side 4.5 mm (SD 0.8)). The two-point discrimination was 4 mm (SD 2) (opposite side 3 mm (SD 1)). The skin healed almost without scarring and the dermal ridges reformed. The regeneration of the soft tissue thickness to almost 90% of its former extent is higher than we expected.